Sport and Democracy in Classical Athens*. (8th February 2017) - Pritchard, David M.
Abstract: This article addresses the neglected problem of elite sport in classical Athens. Democracy may have opened up politics to every citizen, but it had no impact on sporting participation. Athenian sportsmen continued to be drawn from the elite. Thus it comes as a surprise that non-elite citizens judged sport to be a very good thing and created an unrivalled program of local sporting festivals on which they spent a staggering sum. They also shielded sportsmen from the public criticism that was otherwise normally directed towards the elite and its exclusive pastimes. The work of social scientists suggests that the explanation of this problem can be found in the close relationship that non-elite Athenians perceived between sporting contests and their own waging of war. The article's conclusion is that it was the democracy's opening up of war to non-elite citizens that legitimised elite sport.